Analisis Implementasi Sistem Just In Time (JIT) Pada Persediaan Bahan Baku Untuk Memenuhi Kebutuhan Produksi Pada Zidane Meubel Palangka Raya - Rina; Achmad Syamsudin; Deddy Rakhmad Hidayat (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2021)
Purpose, - This research was conducted to determine the most effective use of the raw material inventory method for Zidane Meubel, by comparing the method used by the company to the Just In Time (JIT) method. Desain/methodology/appoach, - This study uses a quantitative descriptive method so that it describes the data with numbers. Findings, - From the analysis using the Just In Time system, it can be concluded that the Just In Time system is more efficient in calculating the total cost of inventory Zidane Meubel.cost savings obtained were Rp 2.095.684,71 from initial invetory Rp 2.900.000.